And There Were the Plitvice Lakes. The Landscapes of the Croatian Lake District in the Romantic Journey Put na Plitvice - Pieniążek-Marković, Krystyna (Poznańskie Studia Slawistyczne, 2023)
Put na Plitvice (The Road to Plitvice, 1860) is the first of the travelogue in Croatian language describing an expedition to the Croatian Lake District. The work of art is of significant “world-creating” and “culture-creating” value, introducing the Plitvice Lakes into the Croatian national text and into the national landscape, hence the biblical allusion in the title. It will therefore be a world-creating narrative, of bringing into existence and therefore giving a symbolic dimension of the work of art.I focus on the landscape-painting aspects of the text, understanding landscape as the manner of constructing and formulating the world, as a way of perceiving and incorporating it into cultural traditions. It is therefore rough, monumental, wild like a traversed space, which should be included in the category of picturesque and sublimity. Veber’s representation of nature illustrates how it was seen at the time within the framework of the national-revival programmes